Focusing on young chindren’s additive and multiplicative reasoning - Mamede, Ema (2012)
This paper describes a brief study to analyse how 4-6-years-old children solve different types of additive and multiplicative reasoning problems. Individual interviews were conducted on kindergarten children when solving the problems. Their performance as well as their explanations were analysed when solving additive and multiplicative reasoning problems. The additive reasoning problems comprised simple, inverse and comparative problems; the multiplicative ones comprised simples and inverse problems. Results suggested that Portuguese kindergarten children have some informal knowledge that allowed them to solve additive and multiplicative reasoning problems with understanding.